IMPROVING DATA ACCURACY IN URBAN ZONING OF AGRICULTURAL LAND - Rukhiddin A. Turaev,; Sanjarbek Z. Safayev, (EPRA International Journal of Research and Development (IJRD), 2022)
In the development of land construction projects for the allocation of agricultural lands to the urban area, among other things, the border lines between the Tashkent region and the city of Tashkent were topographically mapped, and vector layers were developed in the form of point layers and geovisualized in a field view. The total land area of the city of Tashkent was studied using a GPS satellite wave receiver. Field research works were vectorized in a field layer consisting of a total of 784 points on the Tashkent region and 776 points on the border of the city of Tashkent.